Modelización de la calidad del agua del estero El Pital, cantón Quevedo, estación lluviosa, año 2019 - Martínez Arbóleda, Gina Katherine (2019)
The application of mathematical models in water quality serves to determine the behavior of the parameters throughout a stream and set the hydromorphological characteristics. Therefore, the present research aims to model the water quality of the El Pital stream in the rainy season and as the specific objectives: (1) determine the hydromorphological characteristics of the El Pital stream, (2) characterize the water quality of the The Pital stream, (3) model the water quality of the stream with the Streeter-Phelps model, and, (4) simulate the water quality of the El Pital stream with QUAL2K software. To accomplish these objectives, a fieldwork was carried out that included 6 biweekly sampling campaigns during the months of February, March and April, in the rainy season, Seven sampling points were established: upstream, section 1, reach 2, section 3, 1 main discharge from a processing industry of passion fruit (Troprifrutas) and the two main tributaries, one coming from the Promejoras sector and the other is an eye of water that is born from the Gustavo Campi sector. During this phase was included the characterization of the physicochemical parameters of water quality which were: Biochemical oxygen demand (BOD), dissolved oxygen (DO), hydrogen potential (pH), temperature (° C) and electrical conductivity (EC). The mathematical model applied was based on the Streeter-Phelps equations, which allowed modeling the water quality of the El Pital stream, to obtain the BOD and OD profiles. First, the kinetic constants were calibrated the reactive kinetic constants (rearation, deoxygenation and total removal of the BOD), by using statistical software Statgraphics with the Monte Carlo simulation tool, obtaining 10000 possibilities of the constants kinetics Finally, the water quality simulation was carried out using the QUAL2K program, entering the hydrodynamic information of the stream and the calibrated constants Key words: Dissolved Oxygen, Biochemical Oxygen Demand, Water Quality, Streeter-Phelps, calibration, kinetic constants, Monte Carlo simulation, Qual2k.